PENGEMBANGAN SISTEM INFORMASI UNTUK PENGARSIPAN DATA PED (PLANNING, ENGINNER, & DEPLOYMENT) DI TELKOM INDONESIA REGIONAL 1 SUMATERA - Prayogi, Ahmad; Selian, Teguh Agara (Jurnal Media Teknik Elektro dan Komputer, 2025)
Digital transformation in data management has become a strategic necessity for telecommunications companies such as PT Telkom Indonesia, particularly in Regional 1 Sumatra. One of the challenges faced is the manual process of archiving PED (Planning, Engineering, & Deployment) data, which is prone to data loss, delayed access to information, and low operational efficiency. To address these issues, this study aims to develop a web-based data archiving system capable of managing PED data systematically, securely, and easily accessible by authorized users. The system development methodology used is Waterfall, starting from needs analysis, system design, implementation, to testing. The system was built using XAMPP as the development platform, PHP as the backend programming language, and MySQL as the database system. Testing was conducted using the Blackbox method to evaluate system functionality based on real-world user scenarios. The development results show that the system built is capable of effectively handling archiving processes, including document upload features, archive search, metadata input, and user access rights management. This system significantly improves work efficiency, recording accuracy, and data security. Thus, the PED archiving information system is expected to become a digital solution that supports operational transformation in Telkom Indonesia Regional 1 Sumatra.